Developing a Career Information Processing-Based Mobile Cybercounseling Model to Support Senior High School Students’ Career Planning - Eni Fariyatul Fahyuni; Cindy Taurusta; Nurmeini Wulandari; Norzila Binti Ali Musa; Mochamad Nashrullah (International Journal on Integrated Education, 2026)
The rapid development of digital technology requires school guidance and counseling services to provide more accessible, structured, and student-centered career support. This study aims to analyze the development of Mobile Cybercounseling (MCO) based on the Career Information Processing (CIP) framework to support career planning among senior high school students in Sidoarjo Regency. An exploratory mixed-method design was employed by combining Focus Group Discussions with students, guidance and counseling teachers, school leaders, and experts, supported by descriptive student response data. The findings reveal that students experienced several career planning challenges, including limited access to accurate career information, insufficient self-understanding, confusion in choosing study programs or career paths, and psychological barriers to face-to-face counseling. Field data showed that 78.6% of students reported limited access to structured career information, 75.0% experienced confusion in career decision-making, and 85.7% expressed interest in mobile-based career counseling services. The integration of the CASVE cycle—Communication, Analysis, Synthesis, Valuing, and Execution—into the MCO platform was perceived as relevant for guiding students through a systematic career decision-making process. Each MCO feature, including the initial career concern questionnaire, self-assessment, career alternatives, option evaluation, and career roadmap, was aligned with the CIP framework. This study concludes that CIP-based Mobile Cybercounseling is a feasible and theoretically grounded model for supporting structured career planning in senior high schools. Further studies are recommended to examine its effectiveness through broader implementation and experimental testing.